IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AND CREATIVE ACCOUNTING ON FINANCIAL REPORTING QUALITY - Erni Komalasari; Eka Bertuah (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2024)
This research aimed to test whether the implementation of governance in banking in Indonesia influenced the possibility of unethical creative accounting which had an impact on the quality of banking financial reporting. The sample used in this research were accountants who worked at banks in the DKI Jakarta and Bandung areas, totaling 315 respondents. The data analysis technique used was the Structural Equation Model. The research results showed that the implementation of good governance influences the occurrence of unethical creative accounting and the quality of financial reports. The implementation of good governance also influenced the occurrence of creative accounting which had an impact on the quality of financial reports. This showed the importance of implementing good corporate governance in limiting the occurrence of creative accounting which led to unethical actions, to provide reliable quality financial reports for its users. This research contributed to empirical testing of decision-usefulness theory which states the need for rules that must be fulfilled in presenting accounting information reports so that they could be useful in making decisions for users.